Deficiency of Adenosine Deaminase Type 2: A Description of Phenotype and Genotype in Fifteen Cases. Issue 9 (September 2016) - Nanthapisal, Sira; Murphy, Claire; Omoyinmi, Ebun; Hong, Ying; Standing, Ariane; Berg, Stefan; Ekelund, Maria; Jolles, Stephen; Harper, Lorraine; Youngstein, Taryn; Gilmour, Kimberly; Klein, Nigel J.; et al.
Abstract : Objective: To describe the clinical features, genotype, and treatment in a series of subjects with confirmed adenosine deaminase 2 (ADA2) deficiency. Methods: All symptomatic subjects were referred for genetic testing for suspected ADA2 deficiency; relatives of index cases were also screened. Demographic, clinical, and laboratory characteristics and treatments were recorded. Genetic analyses included whole‐exome sequencing in 4 subjects and Sanger sequencing of CECR1 (the gene for cat eye syndrome chromosome region candidate 1) in all subjects. Assays for ADA2 enzyme activity and quantitative polymerase chain reaction analysis of CECR1 messenger RNA (mRNA) were also performed. Results: We identified 15 subjects with ADA2 deficiency, 5 of whom were asymptomatic (relatives of index cases; ages 5–42 years). Homozygous or compound heterozygous mutations in CECR1 were identified in all subjects. Phenotypic manifestations in the patients with symptomatic ADA2 deficiency included livedo racemosa (73.3%), neurologic involvement (53.3%), and immunodeficiency (46.7%). CECR1 mRNA expression in 8 subjects, including 5 who were presymptomatic, was significantly lower than in healthy controls ( P = 0.0016). Subjects with ADA2 deficiency (with or without symptoms) also had lower ADA2 enzyme activity compared to healthy pediatric controls ( P < 0.0001) and patients with sporadic (nonfamilial) childhood polyarteritis nodosa (PAN) without CECR1 mutation ( P = 0.0108). Anti−tumor necrosis factor therapy was required in 9 of the 10 symptomatic subjects. Conclusion: The clinical manifestations of ADA2 deficiency ranged in severity from limited cutaneous involvement to severe multisystemic vasculitis; one‐third of our cases (5 of 15) were currently asymptomatic, and required close monitoring. We recommend CECR1 screening for unaffected siblings of index cases, cases of familial vasculitis, and cases of PAN that is resistant to standard treatment.